Adaptive time-varying formation tracking for multi-agent systems with input saturation via low-gain feedback approach. (April 2023) - Zhang, Xiaoyi; Wu, Jie; Zhan, Xisheng; Han, Tao; Yan, Huaicheng
In this paper, the time-varying formation tracking problem is addressed for a class of multi-agent systems, in which the input of followers is saturated and the input of the leader is unknown. Based on detectable state and undetectable state, a novel kind of protocols is proposed for solving time-varying formation tracking problem, without using any global information for the agents. Then, using the low-gain feedback approach and the Lyapunov stability theory, we can prove that the protocols steer the followers to accomplish and maintain the expected formation and track the leader under the appropriate assumptions. A numerical simulation is provided to verify the performance and effectiveness of our obtained main results.